Signal-to-Noise Ratio dependence on Ground Penetrating Radar antenna frequency in the field of landmine and UXO detection. (September 2015) - Núñez-Nieto, X.; Solla, M.; Gómez-Pérez, P.; Lorenzo, H.
Graphical abstract: Highlights: GPR approach for landmine and UXO detection by SNR. Signal-to-Noise Ratio as function of the signal amplitude and the noise amplitude. Analysis of the SNR versus both vertical and horizontal resolutions. Higher antenna frequencies provided higher SNR. Relationship between the SNR and the size of the target and incident wavelength. Abstract: Ground Penetrating Radar (GPR) is a widely used method in mine and UXO detection. This work presents an analysis of the Signal-to-Noise Ratio dependence on the antenna frequencies most commonly used in demining. The obtained results may be applied to improve the methodology in order to identify targets from SNR. The effectiveness of the method depends on the reflection energy of the GPR wave, directly related with the dielectric contrast between target and medium, and the influence of the antenna frequency. In this sense, different antenna frequencies (2.3 GHz, 1 GHz and 800 MHz) were evaluated; their spatial resolutions were studied and directly related to the SNR values obtained. For a deeper analysis, different plastic mines and metallic UXOs, in homogeneous sandy soil, were used for testing. The results showed that higher frequencies provided higher SNR values. Similar tendencies were observed and negative influences occurred because of resonance scattering, or ringing noise, as well the scattering produced when the target was smaller than the incident wavelength.